A comparison of power controlled flash sintering and conventional sintering of strontium titanate. (15th March 2017) - Lemke, Fabian; Rheinheimer, Wolfgang; Hoffmann, Michael J.
Abstract: The microstructural evolution of SrTiO3 is analyzed during power controlled flash sintering. A controllable sintering process is achieved by lowering the specific power densities yielding a relatively slow flash sintering. The analytical equations for sintering developed by Coble are used to characterize flash sintering. The focus is on the evolution of microstructure with time and its comparison with conventional sintering. The results are discussed in comparison to the active sintering mechanism, the impact of joule heating and to the current state of research on flash sintering of ZrO2 . Graphical abstract: